VARIABILITY OF THE EXTRAGALACTIC RADIO SOURCES 3C120, CTA102, DA55 AND OJ287 ON CENTIMETER WAVES AND ITS CONNECTIONS WITH THE DATA OF VLBI OBSERVATIONS - Ryabov, M.; Donskyh, A.; Suharev, A.; Aller, M. (Одеські астрономічні публікації, 2012)
By data of the long-term monitoring (30- 40 years) fluxes of extragalactic radio sources 3C120, CTA102, DA55 and OJ287 received on the RT-26, University of Michigan present results of data processing with use the wavelet analysis. Received analysis of trend and short-time components of the flux density changes in the studied frequencies 14.5, 8 and 4.8 GHz. For each time components on all frequencies found values of main periods and time of their existence, integrated power spectra for the phases activity for radio sources was built. From the results of VLBI observations in sources with long jets (3C120 and CTA102) detected quasi-periodic structures brighter components. Their appearance is linked to the dynamics of the interaction of shock waves in the jet emission from the cores. Quasi-periodic structures in the jet can be formed as a result of a return standing wave.